2020
DOI: 10.7251/qol2001005s
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Microbiological air Pollution in the Hospital

Abstract: Microorganisms in the air of occupational indoor environments are associated with a wide range of adverse health effects with major public health impact. The aim of this study was testing the presence of microbiological parameters (bacteria and fungi) and microclimatic parameters (temperature and relative humidity) in the clinical hospital “St. Luke the Apostle” in Doboj, which is located in the Republic of Srpska (Bosnia and Herzegovina). Concentrations of bacteria ranged from 35 CFU/m3 to 6,295 CFU/m3. Maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…У састав финих и ултрафиних честица (PM 1 и PM 0,1 ) улазе сулфатни, нитратни и јони амонијума, угљеник, метали (олово, кадмијум, никл, бакар, цинк, магнезијум, жељезо) Снижење нивоа концентрација суспендованих честица може се очекивати једино током периода са повишењем температуре (гашење кућних ложишта као извора загађења у топлом периоду године), повећањем брзине вјетра (одвођење суспендованих честица вјетром), повећањем количине падавина (испирање атмосфере) те снижењем ваздушног притиска, који је обиљежје нестабилног времена и падавина (Илић и Максимовић 2021). (Ilić et al 2018f;Božić et al 2019;Stojanović Bjelić et al 2020;Ilić et al 2020b). Биоаеросоли, као што су ћелије бактерија и гљивица и њихове споре, доприносе 5-34% загађења ваздуха у затвореном простору (Heikkienen et al 2005).…”
Section: озонunclassified
“…У састав финих и ултрафиних честица (PM 1 и PM 0,1 ) улазе сулфатни, нитратни и јони амонијума, угљеник, метали (олово, кадмијум, никл, бакар, цинк, магнезијум, жељезо) Снижење нивоа концентрација суспендованих честица може се очекивати једино током периода са повишењем температуре (гашење кућних ложишта као извора загађења у топлом периоду године), повећањем брзине вјетра (одвођење суспендованих честица вјетром), повећањем количине падавина (испирање атмосфере) те снижењем ваздушног притиска, који је обиљежје нестабилног времена и падавина (Илић и Максимовић 2021). (Ilić et al 2018f;Božić et al 2019;Stojanović Bjelić et al 2020;Ilić et al 2020b). Биоаеросоли, као што су ћелије бактерија и гљивица и њихове споре, доприносе 5-34% загађења ваздуха у затвореном простору (Heikkienen et al 2005).…”
Section: озонunclassified
“…Efficient corrective methods are urgently needed to combat the problem of indoor air quality: bacteria, pollen grains, smoke, humidity, chemical substances, and gases released by anthropogenic activity have adverse health effects on humans. Methicillin-resistantStaphylococcus aureus(MRSA) strainsin long-term care facilities are often more associated with colonialism than clinical infection 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported that an indoor air temperature exceeding 25 o C can cause an increase in fungi growth (Zender-Świercz et al, 2019). It is also suggested that there is a correlation between the amount of fungi and the indoor air temperature (Stojanović Bjelić, Ilić and Farooqi, 2020). Molds produce millions of spores, and they are loosely attached that even slight air currents will disturb the spores, making them airborne.…”
Section: Introductionmentioning
confidence: 99%